Renewable Energy - Resources, Challenges and Applications 2020
DOI: 10.5772/intechopen.91662
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Renewable Energy

Abstract: Offshore renewable technologies hold the potential to satisfy a considerable amount of the global energy demand in the coming years. In this chapter, the main sources of renewable energy related to the oceans (waves, tides, and offshore winds) will be characterized and discussed, with reference to the challenges related to their use. Thus, the main devices capable of exploiting these resources will be presented. Their working principal, together with operational and technological requirements, will be describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In France, offshore renewable energy in Brittany was the case study analysed. It is a sector that is promoted by the Multiannual Energy Programme implemented at the state level, and there are plans to increase the capacity for renewable energy in Brittany [59]. Regarding the environmental aspect of SBG in this case study, from the identified environmental challenges that the sector needs to address, those that were also relevant at the regional level are "the addressing of visual impacts of offshore energy installations and "the difficulty in assessment of trade-offs between environmental benefits from ORE and environmental costs from ORE".…”
Section: Marine Renewable Energy In Francementioning
confidence: 99%
“…In France, offshore renewable energy in Brittany was the case study analysed. It is a sector that is promoted by the Multiannual Energy Programme implemented at the state level, and there are plans to increase the capacity for renewable energy in Brittany [59]. Regarding the environmental aspect of SBG in this case study, from the identified environmental challenges that the sector needs to address, those that were also relevant at the regional level are "the addressing of visual impacts of offshore energy installations and "the difficulty in assessment of trade-offs between environmental benefits from ORE and environmental costs from ORE".…”
Section: Marine Renewable Energy In Francementioning
confidence: 99%
“…These are reviewed and catalogued according to their purpose, characteristics, working principle and underlying methodology. As offshore wind is the most mature technology among ocean renewables, most of the tools have been developed specifically for this technology [19]. Nonetheless, many of these O&M models are flexible or can be easily adapted to other marine renewables [25].…”
Section: Computational Tools For Oandm Planningmentioning
confidence: 99%
“…Several methods have been proposed to fill the gaps and aid the reconstruction of the full dataset [74]. Guidelines, practical aspects, potential and limitations of SCADA and purpose-designed CM systems are provided in [19,56,[75][76][77][78][79][80]. Review papers describing the state-of-the-art in CM systems include [56,67,[81][82][83].…”
mentioning
confidence: 99%